Cardiac magnetic resonance in myocardial disease. Issue 12 (6th June 2006) - Sechtem, U; Mahrholdt, H; Vogelsberg, H
Abstract : For a number of patients it is difficult to diagnose the cause of cardiac disease. In such patients cardiac magnetic resonance is useful for helping to make a differential diagnosis between ischaemic and dilated cardiomyopathy; identifying patients with myocarditis; diagnosing cardiac involvement in sarcoidosis and Chagas' disease; identifying patients with unusual forms of hypertrophic cardiomyopathy and those with continuing myocardial damage; and defining the sequelae of ablation treatment for hypertrophic obstructive cardiomyopathy.